Riang Ria Travel Agency - Aminuddin, Siti Hawa; Lingam, Dg Masliyanie; Francis, Rosalia; Wilod, Allen Alexander; Jamli, Najerah (2015)
This company runs a business relating to the tourism industry which it aims to provide tour and travel services. Basically, the company is providing services like transportations, flight bookings, and accommodations and also touring services for the convenience of all the clients especially the foreign tourists who have never been to Sabah, Malaysia.